Temperature dependent reversal of phase segregation in mixed-halide perovskites - Wright, AD; Patel, JB; Johnston, MB; Herz, LM (Wiley, 2023)
Understanding the mechanism of light-induced halide segregation in mixed-halide perovskites is essential for their application in multijunction solar cells. Here, photoluminescence spectroscopy is used to uncover how both increases in temperature and light intensity can counteract the halide segregation process. It is observed that, with increasing temperature, halide segregation in CH3NH3Pb(Br0.4I0.6)3 first accelerates toward ≈290 K, before slowing down again toward higher temperatures. Such reversal is attributed to the trade-off between the temperature activation of segregation, for example through enhanced ionic migration, and its inhibition by entropic factors. High light intensities meanwhile can also reverse halide segregation; however, this is found to be only a transient process that abates on the time scale of minutes. Overall, these observations pave the way for a more complete model of halide segregation and aid the development of highly efficient and stable perovskite multijunction and concentrator photovoltaics.